A PROSPECTIVE COHORT STUDY ON CLINICAL OUTCOME OF SURGICALLY TREATED ACETABULAR FRACTURE, PATNA, INDIA. - Raman Kumar; Kumar Rahul; Nilesh Kumar Agrawal; Kumar, Santosh (Student’s Journal of Health Research Africa, 2024)
Background The aim of the study is to evaluate the efficacy and outcomes of open reduction internal fixation (ORIF) as a surgical treatment for acetabular fractures. Specifically, the study seeks to assess the restoration of hip function, the incidence of postoperative complications, and the long-term health of the joint following surgical intervention, to determine the effectiveness of this treatment approach across different patient demographics. Method This study was carried out prospectively at the Department of Orthopaedics, IGIMS, Patna for 4 years. In total 50 patients participated in the study. All of them had fractures in their acetabulum. They were treated with open reduction internal fixation surgery for their fractures. screws and plates were used for the reconstruction. The patients followed up for a period of 2 and half years. Results In total 50 patients participated in the study, the outcome of the last follow-up showed that in 80% of the patients, the functional abilities of the hip bone were restored. As for the complications, osteoarthritis was found in 3 patients, Heterotopic ossification was reported in 2 patients, nerve injury in 1, dermal infection in 2, necrosis of the blood vessel in 2, and imperfect reduction in 1 patient. Conclusion Early treatment and longer follow-up improve the outcome of the reduction fixation irrespective of the age and bone health of the patients Recommendation Early diagnosis, treatment, and longer duration of effective follow-up improve the outcome of acetabular fracture reduction.